The art of adornment and make-up in the ancient civilizations of Mesopotamia and the old country of Yemen as a model (Al-Academy, 2022)
This research sheds light on those discrepancies in the use of ornaments, adornment and perfumes, as well as the art of cosmetics, in two important civilizations, namely, the Mesopotamian civilization as the earlier civilization, and the civilization of Yemen, which represents the first Arab civilization. Through the foregoing, our research includes two topics, the first topic included the history of the use of decorations, ornaments and perfumes in the civilization of Mesopotamia, while the second topic included the study of ornaments, adornment and cosmetic art in the ancient civilization of Yemen. And then the research came out with a number of conclusions that the researcher considers very important to highlight the differences and formal methods for the use of adornment, ornaments and cosmetic art between the two civilizations above, and at the end of the research included a list of sources and references adopted by the researcher, which was characterized by the richness of its information about the civilization of Mesopotamia, and said about the ancient civilization of Yemen.